Effect of surface modification on electrochemical performance of nano-sized Si as an anode material for Li-ion batteries. Issue 41 (8th April 2016) - Li, Chao; Shi, Tongfei; Li, Decheng; Yoshitake, Hideyuki; Wang, Hongyu
Abstract : Silicon is one of the most promising anode materials for lithium-ion batteries. Abstract : Silicon is one of the most promising anode materials for lithium-ion batteries. To solve the problems associated with the great volume expansion of Si during lithium storage, nano-sized Si particles are generally employed. However, their high surface activity is likely to trigger considerable electrolyte decompositions at low potential, thus the surface of these Si nano-particles need further chemical modifications. In this paper, three kinds of functional groups were grafted onto the surface of Si particles by different chemical treatments. X-ray photoelectron spectroscopy (XPS) studies proved that the structure of solid electrolyte interface (SEI) film formed on the surface of Si nano-particles depends greatly on the surface modification strategy. Electrochemical characterizations like electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) etc., also verified the distinct effects of these functional groups on the surface of nano-sized Si electrodes. The relationship between surface functional groups and electrochemical performance of the nano-Si anode material was addressed.